PELAKSANAAN COLLABORATIVE GOVERNANCE DALAM PENINGKATAN PEREKONOMIAN DESA MOJOMALANG MELALUI PENGUATAN UMKM - Puspaningtyas, Anggraeny; Radjikan, Radjikan (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2023)
Based on data from the Office of Cooperatives, Industry and Trade, Tuban Regency, in 2019 there were 75,536 MSMEs. The irony is that in Mojomalang Village, Parengan District, there is not much motivation for residents to open their own businesses. The condition of the Mojomalang Village area is a lack of water during the dry season. MSMEs in Mojomalang Village are still underdeveloped because there are many obstacles including a lack of business capital, a lack of understanding on how to grow a business, a lack of product innovation, and product marketing difficulties. During the rainy season, the majority of residents cultivate rice fields and fields to meet their daily needs. However, in the dry season, the residents do not cultivate the fields and fields, but become factory workers. Collaborative governance is the concept of governance in Mojomalang Village in order to improve the village economy through strengthening MSMEs. The purpose of this study is to analyze the implementation of collaborative governance in improving the economy through strengthening MSMEs. The research method used is qualitative with a descriptive approach. Based on the results of the research that has been carried out, it is the collaborative aspect of administering the village government that is more in the aspects of formulating and implementing policies or programs issued by the village government. So that in practice, collaboration in government administration can be said to be less deliberative or deliberative among actors/stakeholders who should be involved. The actors or stakeholders involved in efforts to improve the economy in Mojomalang Village are the village government, MSME actors, BUMDes managers and the community. The recommendation from the research that has been carried out is to develop village potential that involves stakeholders through dissemination. Knowledge of the processing of superior products and the use of appropriate technology can increase the productivity and innovation of MSMEs. So that Mojomalang Village can become a village that has an independent economic power. AbstraksiBerdasarkan data dari Dinas Koperasi, Perindustrian dan Perdagangan Kabupaten Tuban tahun 2019 mencapai 75.536 UMKM. Ironinya, di Desa Mojomalang, Kecamatan Parengan belum banyak motivasi warga untuk membuka usaha sendiri. Kondisi wilayah Desa Mojomalang yang kekurangan air di saat musim kemarau. UMKM di Desa Mojomalang masih kurang berkembang karena banyak kendala diantaranya minimnya modal usaha, kurang memahami cara membesarkan bisnis, kurangnya inovasi produk, dan kesulitan pemasaran produk. Pada musim penghujan, mayoritas warga bercocok tanam di sawah dan ladang untuk memenuhi kebutuhan hidup sehari-hari. Tetapi, pada musim kemarau, warga tidak mengolah sawah dan ladang, tetapi menjadi buruh pabrik. Collaborative governance menjadi konsep penyelenggaraan pemerintahan di Desa Mojomalang dalam rangka meningkatkan perekonomian desa melalui penguatan UMKM. Tujuan dari penelitian ini adalah untuk menganalisis pelaksanaan collaborative governance dalam peningkatan perekonomian melalui penguatan UMKM. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan deskriptif. Berdasarkan dari hasil penelitian yang telah dilaksanakan adalah aspek kolaborasi penyelenggaraan pemerintah desa lebih pada aspek perumusan dan implementasi kebijakan atau program yang dikeluarkan oleh pemerintah desa. Sehingga dalam prakteknya, kolaborasi penyelenggaraan pemerintah dapat dikatakan kurang deliberatif atau musyawarah antar aktor / stakeholders yang seharusnya terlibat. Adapun aktor atau stakeholders yang terlibat di dalam upaya peningkatan ekonomi di Desa Mojomalang adalah pemerintah desa, pelaku UMKM, pengelola BUMDes dan masyarakat. Rekomendasi dari penelitian yang telah dilaksanakan adalah mengembangkan potensi desa yang melibatkan stakeholders dengan diseminasi. Pengetahuan mengenai pengolahan produk unggulan dan penggunaan teknologi tepat guna dapat meningkatkan produktivitas dan inovasi UMKM. Sehingga Desa Mojomalang dapat menjadi desa yang memiliki kekuatan ekonomi yang mandiri.